Social-ecological perspective on the suicidal behaviour factors of early adolescents in China: a network analysis - Xueying Zhang; Yuan Li; Juan Chen; Peiying Li; Mengyuan Yuan; Yonghan Li; Gengfu Wang; Puyu Su (General Psychiatry)
Background In early adolescence, youth are highly prone to suicidal behaviours. Identifying modifiable risk factors during this critical phase is a priority to inform effective suicide prevention strategies.Aims To explore the risk and protective factors of suicidal behaviours (ie, suicidal ideation, plans and attempts) in early adolescence in China using a social-ecological perspective.Methods Using data from the cross-sectional project ‘Healthy and Risky Behaviours Among Middle School Students in Anhui Province, China’, stratified random cluster sampling was used to select 5724 middle school students who had completed self-report questionnaires in November 2020. Network analysis was employed to examine the correlates of suicidal ideation, plans and attempts at four levels, namely individual (sex, academic performance, serious physical illness/disability, history of self-harm, depression, impulsivity, sleep problems, resilience), family (family economic status, relationship with mother, relationship with father, family violence, childhood abuse, parental mental illness), school (relationship with teachers, relationship with classmates, school-bullying victimisation and perpetration) and social (social support, satisfaction with society).Results In total, 37.9%, 19.0% and 5.5% of the students reported suicidal ideation, plans and attempts in the past 6 months, respectively. The estimated network revealed that suicidal ideation, plans and attempts were collectively associated with a history of self-harm, sleep problems, childhood abuse, school bullying and victimisation. Centrality analysis indicated that the most influential nodes in the network were history of self-harm and childhood abuse. Notably, the network also showed unique correlates of suicidal ideation (sex, weight=0.60; impulsivity, weight=0.24; family violence, weight=0.17; relationship with teachers, weight=−0.03; school-bullying perpetration, weight=0.22), suicidal plans (social support, weight=−0.15) and suicidal attempts (relationship with mother, weight=−0.10; parental mental illness, weight=0.61).Conclusions This study identified the correlates of suicidal ideation, plans and attempts, and provided practical implications for suicide prevention for young adolescents in China. Firstly, this study highlighted the importance of joint interventions across multiple departments. Secondly, the common risk factors of suicidal ideation, plans and attempts were elucidated. Thirdly, this study proposed target interventions to address the unique influencing factors of suicidal ideation, plans and attempts.